2011
DOI: 10.1038/eye.2010.226
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for visual outcomes 2-years after intravitreal bevacizumab for myopic choroidal neovascularization

Abstract: Purpose To determine the pre-treatment ocular factors significantly associated with the visual outcome 24 months after intravitreal bevacizumab (IVB) for myopic choroidal neovascularization (mCNV). Methods A total of 23 eyes of 23 patients with mCNV were treated with IVB followed by as needed therapy. The efficacy of IVB was evaluated by the best-corrected visual acuity (BCVA) at 24 months after the initial treatment. Forward stepwise multiple linear regression analyses were performed to evaluate the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 32 publications
8
50
0
3
Order By: Relevance
“…In addition, we also found that the size of myopic CNV was negatively correlated with the extent of visual improvement at 2 years. The result supports the findings by Nakanishi et al, 28 in which the size of myopic CNV is a significant factor in influencing the final visual acuity after intravitreal bevacizumab treatment.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, we also found that the size of myopic CNV was negatively correlated with the extent of visual improvement at 2 years. The result supports the findings by Nakanishi et al, 28 in which the size of myopic CNV is a significant factor in influencing the final visual acuity after intravitreal bevacizumab treatment.…”
Section: Discussionsupporting
confidence: 82%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Although the short-term results have demonstrated significant visual improvement following anti-VEGF therapy, the longer term visual outcomes appeared more variable. 14,[26][27][28] In addition, many previous studies have included both treatment naïve cases and previously treated eyes, as well as subfoveal and non-subfoveal CNV in the series, making comparison of results more difficult. The main strengths of our current study included the relatively long follow-up duration of 2 years and the homogeneity of cases with only treatment naïve subfoveal myopic CNV included in the series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De facto, uma melhor MAVC inicial está associada a menos dano nos fotorreceptores, que poderá explicar os melhores resultados. 15,25 No entanto, outros estudos mostram que uma MAVC inicial mais baixa cursa com melhores resultados após tratamento, 13 de acordo com o ceiling floor effect. Os autores consideram que uma melhor MAVC inicial terá menor probabilidade de melhorar (ceiling effect), enquanto doentes com pior MAVC inicial terão mais probabilidade de melhorar (floor effect).…”
Section: Discussionunclassified
“…[17][18][19][20] Surgiu assim a necessidade de introduzir novas terapêuticas, nomeadamente as injecções intravítreas de agentes anti-VEGF, que mostraram melhores resultados no tratamento. 4,6,[21][22][23][24][25] A terapêutica antiangiogénica, nomeadamente o bevacizumab e o ranibizumab, estão aprovados para o tratamento da neovascularização coroideia secundária à degenerescência macular da idade (DMI), tendo também mostrado claros benefícios clínicos na neovascularização associada a outras situações de causa inflamatória ou vascular. 3,9,26 Face à evidência de eficácia e segurança com o uso destes agentes, a sua utilização na NVC associada à miopia patológica é atualmente considerada terapêutica de primeira linha.…”
Section: Introductionunclassified